RC6 Key Generation Method using Permutation Last Layer Algorithm - Zaki, Rana M; Abdul Wahab, Hala Bahjat; Mahdi, Zaed S (Iraqi Journal of Science, 2025)
Long Term Evolution-LTE is a mobile communication system used in wireless communication networks, while the development of communication methods used today and the high demand for mobile devices of all kinds have necessitated many attacks. This paper suggests a new way to model and build the RC6 algorithm, which creates dynamic keys using last-layer switching (PLL) algorithms, so that it can be used for more than just text and images in a 4G network. Images of different lengths and sizes are selected in the encryption and decryption process. Comparative results show that the proposed security algorithms outperform the standard algorithms. A lot of tests were done on both algorithms, and the proposed algorithm did better than the standard ones in many areas. These included execution time analysis, production encryption and decryption analysis, block-based analysis, potential security vulnerabilities in analysis and key search, statistical tests, entropy, correlation coefficient (CC), and capture-to-signal noise ratio (PSNR). All these criteria prove satisfactory security and good randomness in the proposed algorithm